SISTEM PENGOLAHAN DAN ANALISIS KUALITAS AIR MINUM SECARA FISIKA DAN KIMIA DI PDAM TIRTAMARTA YOGYAKARTA BERDASARKAN PERMENKES NOMOR 907/MENKES/SK/VII/2002 DALAM UPAYA PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) TUJUAN 6 - Agus Candra (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2018)
PDAM Tirta Darma Yogyakarta is a Yogyakarta Regional Water Supply Company which is a clean water treatment company that processes raw water from 4 sources, namely springs, rivers, shallow wells, and deep wells which have several processing operations locations which are scattered in various places.The method used in this study is interviews and literature studies with Qualitative analysis, Quantitative analysis aims to determine the amount / level of a substance contained in water. The analysis included several tests, namely determination of pH, determination of chlorine residue, determination of iron content, determination of nitrite content, determination of manganese content, and determination of water hardness. Furthermore, the measurement results are compared with the water quality standards that have been determined. Based on the decree of the Indonesian Minister of Health NO. 907 / MENKES / SK / VII / 2002. Based on the results of the study of Chemical Water Quality Analysis, PH, Chlorine Residue and Iron Content. Processed water in the PDAM TirtaMarta Yogyakarta IPAM that has met the quality standards for drinking water quality standards ... Water Quality Analysis Physically. Color, Temperature / Temperature, Turbidity, Odor and Taste. Processed water in PDAM Tirtamarta Yogyakarta's IPAM In accordance with the criteria of drinking water in general Based on the decree of the Indonesian Minister of Health NO. 907 / MENKES / SK / VII / 2002